Design and characterization of an OPV-ETFE multi-layer semi-transparent glazing. (November 2022) - Moreno, A.; Riverola, A.; Chemisana, D.; Vaillon, R.; Solans, A.
Abstract: Architectural glazing has several advantages in terms of aesthetics and user well-being perspectives. However, they can have large impacts on heating and cooling demands and artificial lighting requirements. Ethylene tetrafluoroethylene (ETFE) cushion systems present adequate insulating and transparency characteristics, and, combined with organic photovoltaic (OPV) modules, become a glazing element leading towards energy efficient buildings. The present manuscript reports on a detailed optical, thermal and electrical analysis of a 3-layer ETFE/ OPV cushion that helps the design of these glazing-type systems by providing a better understanding of their performance. Spectrophotometric optical measurements up to 50 μ m allow proper estimations of an individual layer radiative behavior. As a matter of fact, these measurements feed the radiative and thermal models that aim at determining the behavior of the organic photovoltaic module as a function of its position in the cushion. Based on the organic photovoltaic module spectral response, electrical power production is estimated. Results reveal that the best configuration is the one placing the organic photovoltaic module in the outer layer, since it represents the case where the OPV module performs better due to the higher incident irradiance and the low dependency on temperature of the generated power.